2020
DOI: 10.3390/su12010374
|View full text |Cite
|
Sign up to set email alerts
|

Responsible Agricultural Mechanization Innovation for the Sustainable Development of Nepal’s Hillside Farming System

Abstract: Agricultural mechanization in developing countries has taken at least two contested innovation pathways—the “incumbent trajectory” that promotes industrial agriculture, and an “alternative pathway” that supports small-scale mechanization for sustainable development of hillside farming systems. Although both pathways can potentially reduce human and animal drudgery, the body of literature that assesses the sustainability impacts of these mechanization pathways in the local ecological, socio-economic, cultural, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 48 publications
(106 reference statements)
1
33
0
1
Order By: Relevance
“…Previous studies showed that the realization of mechanization is impossible or uneconomic for a developing country with millions of small households [41][42][43]. However, mechanization has been successfully developed in these countries, such as India, Nepal, China and African countries [11,15,16,[44][45][46][47]. As a role model, China has achieved great success in terms of mechanization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the realization of mechanization is impossible or uneconomic for a developing country with millions of small households [41][42][43]. However, mechanization has been successfully developed in these countries, such as India, Nepal, China and African countries [11,15,16,[44][45][46][47]. As a role model, China has achieved great success in terms of mechanization.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the immediate income gain by increased crop yield (Liu et al, 2015) and the second is the negative ecological disturbance and human health degradation over the long run, which far outweighs the first effect (Antle and Pingali, 1994;Pimentel, 1996;Krebs et al, 1999;Tilman et al, 2001;Atreya, 2008;Pingali, 2012). Evidence shows that prevailing agricultural policies have led to this environmental crisis by favoring large farm size, specialized production, crop monocultures and mechanization (MoAD, 2014;Norgrove and Hauser, 2015;Devkota et al, 2020). As a result, assemblages of farm components are broken; nutrient and energy cycles are more open; pest outbreaks often occur; plants become more susceptible to pests; insects develop resistant to pesticides; often small farm-holders are marginalized or pushed out of agriculture (Dhanagare, 1988;Altieri and Nicholls, 2001;Altieri, 2004Altieri, , 2018; and finally, the high chemical input-based agriculture becomes unsustainable (Shiva, 1992;Wilson, 2000;FAO, 2017).…”
Section: The High Input-based Agriculture Is Unsustainablementioning
confidence: 99%
“…For example, a picture lesson was shown that introduced the women farmers to a seed drill planter (jab planter, Figure 5) intended to mitigate male outmigration that has caused declines in the traditional male-dominated practice of livestock plough-based sowing. In the lesson, to illustrate the traditional practice, a female farmer was shown ploughing the land using oxen; however, women are not allowed to plough land using livestock in the local Hindu culture [41]. As a result, during participatory discussions, most of the women farmers stated that they were offended by this image and asked for it to be changed (see edit request, upper left in Figure 5, and an edited version in Figure 6).…”
Section: Findings Related To Gender Specific Editsmentioning
confidence: 99%